MODELLING OF PROCESSES OF HEAT EXCHANGE AT VIBRATING INFLUENCE IN MULTICOMPONENT MIXTURES OF BIOREACTORS - Ratushnyak, Georgij; Djedjula, Vyacheslav (Scientific Works of Vinnytsia National Technical University, 2015)
The basic laws of thermal and hydrodynamic processes in multicomponent organic mixes are considered at vibration action. Results of research allow to define parameters of heat-exchange devices in reactors of food, processing, chemical areas and for biogas production.